Cleaner Production Initiatives in a Diesel Engines Factory - Pinto, Luiz Fernando Rodrigues; Oliveira Neto, Geraldo Cardoso de; Mummolo, Giovanni; Digiesi, Salvatore; Facchini, Francesco; Centoamore, Plinio (International Journal of Industrial Engineering and Management, 2020)
This paper presents a case study conducted in a Diesel engines manufacturer, which adopted a Cold Test machine to perform the final check of engines in the assembly line. The overall aim of this investigation was evaluating the economic and environmental advantages obtained by the adoption of the Cold Test machine. The results showed cost saving of USD 558,012.67 per year. The investment required, USD 2.1millions, returned in three years and ten months. The environmental assessment identified the reduction of the mass intensity per abiotic, biotic, water and air compartments, total of 178,420,306.06 kg resources conservation per year. Article history: Received (September 25, 2019); Revised (February 12, 2020); Accepted (February 18, 2020); Published online (March 26, 2020)